(untitled) (Al-Academy, 2016)
It’s for sure that TV or cinematic production requires an effort that is described to be large according to the script , thus we find a production sectors that couldn’t fulfill these tasks especially in Iraq for its current challenges , although we found the department of film & television have a large quantity that could be described as big comparing to the Iraqi production sectors , alongside what it does provides to the Iraqi dramatic movement , but the cause that the management of this department is looking for is the quality that osmosis an dramatic & atheistic value , this production quantity that is productions operations frequently is attacked by lagging that came from many reasons that " May or May not " known to the specialists in the area of production management , that encouraged the researcher to study the reality of students film production in the department of film & television , to analyses this stats than diagnosing the dilemmas reaching to its solutions , to gain the benefits of this research to avoid the mistakes for production operations to this prestige’s department